KUALITAS PELAYANAN KESEHATAN DENGAN MINAT BEROBAT KE PUSKESMAS LIMBOTO KABUPATEN GORONTALO - Haslinda Damansyah; Rahmat Kadir (-, 2021)
This research was conducted in social health center ofLimboto. The aimed of research to determine the relationship between independent and dependent variables. In addition, researchers want to know their patients' satisfaction after treatment at Social Health Center of Limboto. This research use quantitative descriptive method with cross sectional approach. The totals sample of 60 people. Taken sampling bytotal sampling. This research used traditional statistical test Spearman Rho. The result showed that (p) = 0,00<α = 0.05. While using statistical tests obtained Spearman Rho correlation coefficient (r) = 0.77 with high-level relations / strong. The conclusion that there is a relationship between the qualities of health services to the people's interests went to the social health center of Limboto Gorontalo regency.